2021
DOI: 10.1037/xlm0001054
|View full text |Cite
|
Sign up to set email alerts
|

The congruency sequence effect is modulated by the similarity of conflicts.

Abstract: The congruence effect can be modulated by adjacent conflict conditions, producing the congruency sequence effect (CSE). However, many boundary conditions prevent the transfer of the cross-conflict CSE. A consensus has been achieved that the CSE reflects both top-down control and bottom-up associative learning, but neither perspective could perfectly interpret the various boundary conditions. Their imperfections recently inspired an integrative learning account of cognitive control, which predicts that conflict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(29 citation statements)
references
References 58 publications
6
23
0
Order By: Relevance
“…Behaviorally, we found that the CSEs were linearly modulated by conflict similarity between consecutive trials, replicating and extending our previous study (Yang et al, 2021). BOLD activity patterns in the right dlPFC further showed that the representational similarity between conflict types was modulated by their conflict similarity, and that strength of the modulation was positively associated with the modulation of conflict similarity on the behavioral CSE.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Behaviorally, we found that the CSEs were linearly modulated by conflict similarity between consecutive trials, replicating and extending our previous study (Yang et al, 2021). BOLD activity patterns in the right dlPFC further showed that the representational similarity between conflict types was modulated by their conflict similarity, and that strength of the modulation was positively associated with the modulation of conflict similarity on the behavioral CSE.…”
Section: Discussionsupporting
confidence: 90%
“…Experiment 1 Experimental Design. We adopted a modified spatial Stroop-Simon task (Yang et al, 2021) (Fig. 1).…”
Section: Methods Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…While trial-by-trial explicit cues often do not result in smaller congruency effects, experience-based control is well known to produce such effects, in the shape of the so-called congruency-sequence effects, whereby an incongruent N-1 trial results in a smaller congruency effect on trial N, arguably due to an up-regulation of control. In line with other recent studies (e.g., Dignath et al, 2019; Grant et al, 2020; SpapĂ© & Hommel, 2008), Yang et al (2021) here showed that this effect, too, involves an associative learning component. Specifically, the degree to which this effect is expressed depends on the similarity of the control demands across trials.…”
Section: Theme 2: How Learning Of the Likelihood Of Control Demand Di...supporting
confidence: 94%